Design and Analysis of Beam with Opening using Strut and Tie Model - Doris, Ahmad; Kurniawan, Ruddy; Thamrin, Rendy (Universitas Negeri Padang, 2023)
Concrete beams on structures sometimes have to be covered for utility lines. For the case of concrete beams with openings, special calculations must be made because the lengths of the dimensions no longer have the same dimensions. One of the approaches is with the strut and tie model. Currently, there are no standard provisions in the manufacture of the strut and tie model, as it is an approach to calculating in areas where Bernoulli's law does not apply. In order to facilitate the creation of a strut and tie model, the study used a simple software tool called BESO2D. The number of samples of the test model is 4 variations with different position and size of the hole. The dimensions of the beam used are 150x300 mm with a length of 2000 mm. Each of the beams will be given a reinforced based on the working load and from the strut and tie model frame. The behavior of each beam will be analyzed using the software of the finite element method to specific concrete named ATENA.